2016
DOI: 10.2214/ajr.16.16078
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists' Training, Experience, and Attitudes About Elder Abuse Detection

Abstract: OBJECTIVE Elder abuse is underrecognized, and identification of subtle cases requires a high index of suspicion among all health care providers. Because many geriatric injury victims undergo radiographic imaging, diagnostic radiologists may be well positioned to identify injury patterns suggestive of abuse. Little is known about radiologists’ experience with elder abuse. Our goal was to describe knowledge, attitudes, training, and practice experience in elder abuse detection among diagnostic radiologists. SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…These low reported rates of elder abuse, both in our study and in the literature, also align with larger epidemiological studies that report significant under-recognition of the problem (Fulmer, 2003;Touza Garma, 2017). In prior, interview-based qualitative studies, both radiologists and EM physicians reported believing that a lack of adequate training had led them to miss cases of elder abuse, and expressed desires for more training on the subject (Rosen, Bloemen, et al, 2016;Rosen, Hargarten, et al, 2016). Our interviews were also consistent with these findings and showed an overwhelming consensus across disciplines that elder abuse was both lacking and desired from training curricula.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These low reported rates of elder abuse, both in our study and in the literature, also align with larger epidemiological studies that report significant under-recognition of the problem (Fulmer, 2003;Touza Garma, 2017). In prior, interview-based qualitative studies, both radiologists and EM physicians reported believing that a lack of adequate training had led them to miss cases of elder abuse, and expressed desires for more training on the subject (Rosen, Bloemen, et al, 2016;Rosen, Hargarten, et al, 2016). Our interviews were also consistent with these findings and showed an overwhelming consensus across disciplines that elder abuse was both lacking and desired from training curricula.…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of elder abuse has been estimated to be as high as 10% in the US (Burnes et al, 2015;C. Cooper et al, 2009;Rosen, Hargarten, Flomenbaum, & Platts-Mills, The health care system, and the emergency department (ED) in particular, has been proposed as providing an important "window of opportunity" to screen patients for elder abuse (Kahan & Paris BE, 2003;Rosen, Bloemen, et al, 2016). Health care providers in the ED are uniquely positioned to detect and report abuse, as they are often the only contact that victims have outside their families (Touza Garma, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muitos profissionais da saúde reconhecem não saber como intervir e promover de forma pragmática a discussão no contexto social, além isso desconhecem a quem recorrer quando se deparam com um idoso vítima de violência; ademais, frequentemente existem sentimentos de receio e medo por parte do idoso de mencionar que sofreu agressão, por desconfiar dos serviços de apoio e proteção da pessoa idosa ou por temer que os familiares e/ou o agente agressor acabem por descobrir ( OLIVEIRA et al, 2018). Principalmente porque os idosos tem receio que ao denunciar sofram represália dos familiares e/ou do agente agressor (ROSEN et al, 2016).…”
Section: Discussionunclassified
“…Emergency radiologists are contributing additional concerning findings indicative of elder abuse, 38,41,42 such as the concomitant presence of old and new fractures, high-energy fractures inconsistent with the purported mechanism, and distal ulnar diaphyseal fractures. 41,42 The ultimate goal is to identify pathognomonic injury patterns similar to those found in child abuse cases, to assist ED providers.…”
Section: Imaging Studiesmentioning
confidence: 99%